2022
DOI: 10.1111/gwao.12830
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional identities and career progression in retail: The experiences of minority‐ethnic women

Abstract: Contributing to scholarship on diversity and inclusion (D&I) and careers within UK retailing, this paper documents the lived experiences of minority-ethnic women working in retail. Given the extensive research on both the career obstacles faced by women in a highly feminized sector and the disadvantages experienced by minority-ethnic workers in the UK labor market more broadly, consideration of social identity categories beyond gender and their impact on retailing careers in the existing literature is limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Unfortunately, 6 these demands continue as a survey of 2000 women of colour in UK revealed that 61% had to modify their language, discussions, hairstyles, diet, or even their names to fit in at work (Gyimah et al, 2022). There is limited understanding towards workplace experiences among racially diverse women retail workers (Kele et al, 2022;Opara et al, 2020). Further research is needed to explore their experiences, and how different aspects of aesthetic labour may be demanded and controlled by employers.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Unfortunately, 6 these demands continue as a survey of 2000 women of colour in UK revealed that 61% had to modify their language, discussions, hairstyles, diet, or even their names to fit in at work (Gyimah et al, 2022). There is limited understanding towards workplace experiences among racially diverse women retail workers (Kele et al, 2022;Opara et al, 2020). Further research is needed to explore their experiences, and how different aspects of aesthetic labour may be demanded and controlled by employers.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Nevertheless, workplace experiences of ethnic minority workers in the UK are relatively underexplored (Opara et al, 2020;Ozturk & Berber, 2022). It is found that women of colour working for UK retailers are disproportionately disadvantaged in their career progression whilst managers and directors in this field are mostly White male (Kele et al, 2022). Further studies examining the workplace experiences of ethnic minority women workers are much needed (Kele et al, 2022;Opara et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations